Management of palpitations and cardiac arrhythmias in pregnancy. (22nd August 2019) - Roberts, Anna; Mechery, Joseph; Mechery, Anthony; Clarke, Bernard; Vause, Sarah
Abstract : Key content: Palpitations are common in pregnancy; while they are frequently benign, some will represent a significant arrhythmia. Pregnant women presenting with palpitations require a careful assessment to determine whether their symptoms can be attributed to normal physiology or require further investigation for pathology. Management of pre‐existing arrhythmias in pregnancy requires a multidisciplinary team approach. Most anti‐arrhythmic treatments are safe in pregnancy, and prompt, effective treatment of pathological arrhythmias should be instigated without delay. Learning objectives: To identify which women presenting with palpitations require further investigation. To understand normal changes in the electrocardiogram in pregnancy and be able to identify common arrhythmias. To understand the principles of management of common cardiac arrhythmias during pregnancy. To know the risks and benefits of common anti‐arrhythmic drugs in pregnancy and breastfeeding.